A model to predict ventilator requirement in myotonic dystrophy type 1. Issue 6 (2nd April 2019) - Vivekananda, Umesh; Turner, Chris
ABSTRACT: Introduction: Respiratory failure is one of the most common causes of mortality in myotonic dystrophy type 1 (DM1). The variation in the DM1 phenotype causes difficulty in clinically predicting the severity of respiratory involvement, and variables such as daytime somnolence are insensitive for identifying patients who require continuous or bilevel nocturnal positive airway pressure (NPAP). Methods: We retrospectively analyzed a cohort of 126 adult onset patients with DM1 at the point of their first respiratory assessment to identify significant factors in predicting ventilator requirement. Results: Triplet repeat years score and Muscle Impairment Rating Scale were significantly linearly related to NPAP and, thus, formed the model. Discussion: We devised a simple model to aid clinicians in predicting at first visit those patients with DM1 who are likely to require NPAP. We also describe the causes of failure to tolerate NPAP in DM1. Muscle Nerve 59:683–687, 2019